2018
DOI: 10.1002/jcb.27285
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals an altered expression profile of zinc transporters in colorectal cancer

Abstract: Zinc is a transition metal and catalytic cofactor involved in many biological processes including proliferation, development, differentiation, and metabolism. Zinc transporters (ZnTs) play a fundamental role in cellular zinc homeostasis. ZnTs are responsible of zinc efflux and are encoded by 10 genes belonging to solute carrier family 30A (SLC30A1-10), while zinc-regulated transporter (ZRT)/iron-regulated transporter (IRT)-like protein (ZIP) transporters are responsible for the influx of zinc into the cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 45 publications
(133 reference statements)
2
35
0
Order By: Relevance
“…ZIP6 has been implicated in oesophageal cancer [70,71], breast cancers [23] prostate cancer [72], consistently being associated with more aggressive forms of the diseases. Similarly, ZIP10 over-expression has been correlated to aggressiveness in renal cell carcinoma [36], metastatic breast cancer [35], gastric cancer [73] and it is one of the 7 zinc transporter genes upregulated in activated colon tumour cells [24], compatible with our proposed role for ZIP10 in cell division.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…ZIP6 has been implicated in oesophageal cancer [70,71], breast cancers [23] prostate cancer [72], consistently being associated with more aggressive forms of the diseases. Similarly, ZIP10 over-expression has been correlated to aggressiveness in renal cell carcinoma [36], metastatic breast cancer [35], gastric cancer [73] and it is one of the 7 zinc transporter genes upregulated in activated colon tumour cells [24], compatible with our proposed role for ZIP10 in cell division.…”
Section: Discussionsupporting
confidence: 61%
“…Accordingly, chelating zinc has been explored as a means to stop proliferative growth of cancer tissues [22]. The additional zinc seen in cancers is usually supplied by various zinc transporters from the SLC39A family [23] [24][25][26]. Two close homologues within this family, ZIP6 (SLC39A6, also known as LIV-1) and ZIP10 (SLC39A10) [27,28], with a 43.5% sequence identity, are on the same clade of the ZIP family phylogenetic tree [29] and have both been independently implicated in cancer [23,29].…”
Section: Cellular and Molecular Life Sciencesmentioning
confidence: 99%
“…High expression levels of SLC39A10 have been reported to be correlated with invasive behaviour by stimulating cell migration in breast cancer cells [44]. Similar observations have been made in the case of colorectal cancer [45] and renal cell carcinoma [46]. Cao et al (2019) [16] demonstrated that SLC39A10 was down-regulated in GBM tissues and positively associated with survival which is consistent with our finding in this study, but its role in GBM progression is poorly understood and requires further exploration in future studies.…”
Section: Discussionsupporting
confidence: 58%
“…SLC30A4 is significantly overexpressed in prostate cancer compared to normal tissues from other organs 22 . SLC30A5-7 and 9 are significantly upregulated in colorectal cancer and SLC30A9 is involved in the canonical Wnt pathway 24 . Overexpressed SLC30A7 in esophageal squamous cell carcinoma could be a mechanism adapted by tumor cells to maintain the basal zinc requirement for carrying out vital functions during zinc deficiency 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that SLC30A1 , 9 and 10 were significantly upregulated in prostate cancer tissues compared to normal tissues, while SLC30A5 - 6 were strongly downregulated 21 23 . Upregulated SLC30A5-7 expression might play a critical role in coordinating transcriptional programming associated with the increased activity of the early secretory pathway in colorectal cancer 24 . Nevertheless, the functional and prognostic significance of SLC30A family genes in GC remains unclear.…”
Section: Introductionmentioning
confidence: 99%